Temple Theology, Holistic Eschatology, and the Imago Dei: An Analytic Prolegomenon - Turner, J. R., James T. (TheoLogica, 2018)
In this paper, I offer something of a prolegomenon, outlining some areas in which certain strands of biblical theology and analytic theological reflection can be mutually informative. To do so, my paper unfolds in three ways. In the first section, I provide some reasons to think that biblical theologians are onto a reading of Scripture that merits the attention of analytic theologians. In section II, I outline some areas in the biblical theological data that would benefit from analytic exploration and reflection. Finally, in sections III and IV, I present a test case: the imago Dei and the importance of the future bodily resurrection. This should help show how this strand of biblical theology and analytic theological reflection can be mutually informative.